The Orvan Brook Volcanogenic Massive Sulfide Deposit: Anatomy of a Highly Attenuated Massive Sulfide System, Bathurst Mining Camp, New Brunswick - J. A. Walker; D. R. Lentz; S. H. Mcclenaghan (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
"Abstract - The Orvan Brook deposit is one of several (Zn+Pb>>Cu)-rich sulfide deposits hosted by the Spruce Lake Formation (California Lake Group) in the northwestern part of the Bathurst Mining Camp. This parautochthonous deposit is hosted by a narrow band of highly deformed, locally graphitic shale that appears to conformably overlie felsic volcanic rocks of the Spruce Lake Formation, and is in tectonic contact with overlying mafic volcanic and related sedimentary rocks of the Canoe Landing Lake Formation. The Spruce Lake Formation is dominated by felsic volcanic rocks and subordinate fine-grained sedimentary rocks, and mafic volcanic rocks (Canoe Landing Lake member). The felsic volcanic rocks can be divided into aphyric and feldspar-phyric rock types. The feldspar-phyric rocks and a few of the aphyric varieties have a Zr/TiO2 ratio of 0.06, and fall into the California Lake Group field on a Y/TiO2 versus Zr/TiO2 diagram. In contrast, the aphyric felsic volcanic rocks have Zr/TiO2 ˜ 0.09 and are marked by high Zr and Th, which is consistent with highly fractionated felsic magma of Spruce Lake affinity. Major and trace element analyses of host rocks suggest that weak to moderate hydrothermal alteration developed on the south side (stratigraphic footwall) of the deposit, which is consistent with a north-younging succession. The sulfide lens strikes east-west for approximately 2.3 km, extends down-dip for at least 500 m locally, and has an average thickness of between 0.75 and 1 m, but is locally up to 5.5 m thick. The contacts of the massive sulfide lens with its host rocks are invariably sharp. Host rocks show evidence of intense ductile deformation as well as later brittle deformation. Compositional layering and sulfide breccia textures in the sulfide body are interpreted to result from deformation or tectonic enhancement of original primary layering. The deposit contains an estimated resource of 2.69 Mt grading 1.73% Pb, 5.95% Zn, 0.37% Cu, 72 g/t Ag, and 0.9 g/t Au. Similarities in bulk d34S between the Orvan Brook (+8.6‰) and the nearby Cu-rich McMaster deposit (+8.2‰) suggest a common depositional setting."